Vehicle Propulsion Systems Introduction to Modeling and Optimization - Guzzella, Lino.; Sciarretta, Antonio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
Automobiles are responsible for a substantial part of the world's consumption of primary energy, mostly fossil liquid hydrocarbons. The reduction of the fuel consumption of these vehicles has become a top priority. Many ideas to reach that objective have been presented. In most cases these systems are more complex than the traditional approaches. For such complex systems a heuristic design approach fails. The only way to deal with this situation is to employ model-based methods. This text provides an introduction to the mathematical modeling and subsequent optimization of vehicle propulsion systems and their supervisory control algorithms.
Vehicle Energy and Fuel Consumption — Basic Concepts -- IC-Engine-Based Propulsion Systems -- Electric and Hybrid-Electric Propulsion Systems -- Non-electric Hybrid Propulsion Systems -- Fuel-Cell Propulsion Systems -- Supervisory Control Algorithms -- Appendix I — Case Studies -- Appendix II — Optimal Control Theory -- Appendix III — Dynamic Programming.
Keywords: Mechanical engineering; Automotive engineering; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Control engineering; Robotics; Mechatronics; Energy systems; Transportation; Mechanical Engineering; Automotive Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Control, Robotics, Mechatronics; Energy Systems; Transportation